An optimization model for doctors’ schedules at Landspítali : The National University Hospital of Iceland - Sigrún Bryndís Gylfadóttir 1992- (2019)
Making a fair and functional staff schedule can be a big challenge for most companies. It can take days or up to weeks to develop a feasible schedule. Every staff scheduling problem is different from each other when considering the various requirements of companies and employees. The main goal of this thesis is to improve and construct a staff schedule for foundation doctors in the Internal Medicine Department, which is the largest department of Landspítali - The National University Hospital in Iceland. Constructing a fair schedule has a high impact on doctors working conditions; it is also crucial that the department is not understaffed — better staff scheduling results in better health care. Today the doctor schedule in the department is mostly done manually, which is a time-consuming task and increases the likelihood of errors. A mathematical model, using integer linear programming was created for the scheduling problem in the department. The model captures the realistic constraints related to the problem, such as Icelandic wage agreements and hospital policies. One of the main scheduling problems in the department is fulfilling the vacation hours that the employees earn after shifts that are longer than eight hours, the mathematical model solves this problem well. The results show that a feasible solution can be found with automation that meets more requirements than the current schedule, and the scheduling time is much less. Fyrir flest fyrirtæki getur það verið stór áskorun að útbúa sanngjarnt vaktaplan sem virkar eins vel og til er ætlast. Það getur tekið frá nokkrum dögum upp í margar vikur að þróa hagkvæmt plan. Hvert fyrirtæki og starfsfólk hafa mismunandi þarfir, þ.a.l. eru lausnirnar við vandmálinu ekki allar eins þar sem hvert vaktaplan hefur sín vandamál. Megin markmiðið með þessari ritgerð er að betrumbæta og byggja upp vaktaplan fyrir lækna á lyflækningasviði Landspítalans sem er stærsta svið spítalans. Að útbúa sanngjarna og hagkvæma vaktaáætlun getur haft mikil áhrif á vinnuskilyrði læknanna, ...